Estimating the Impact of Fundamental Macroeconomic Factors on the Capital Market: A MIDAS Approach - Reza Tehrani; Mahmoud Moktarband; Menal Aboodeh (تحقیقات مالی)
ObjectiveAs one of the pillars of financing countries, the stock market plays a key role in the prosperity of economic activities. The key position of the stock market has caused much research to be conducted to identify the factors affecting it. The stock market serves as a platform that incentivizes savers to invest their surplus resources in shares of economic enterprises or securities. This mechanism plays a crucial role in enhancing investment and fostering economic growth. By facilitating the flow of funds from savers to investors, the stock market contributes significantly to overall economic development. This study aimed to investigate the effects of macroeconomic variables on the stock market, employing a self-regression method that incorporates distribution breaks, alongside a Mixed Data Sampling (MIDAS) approach to handle data with different frequencies. MethodsThe MIDAS approach is a specialized regression technique characterized by independent variables having a higher frequency than the dependent variable. This method involves a trade-off between the advantages of utilizing more data and the costs associated with estimating additional parameters. The fundamental variables analyzed in this research include gross domestic product (GDP), interest rates, oil prices, exchange rates, and inflation. In this research, after conducting the necessary statistical tests for both explanatory and dependent variables, the study period was determined to span from 1990 to 2020. ResultsThe results of the MIDAS model indicate that oil prices, liquidity, and exchange rates positively and significantly influence stock market behavior, serving as explanatory factors for the stock market index over the long term. The previous proposition indicates that increases in the aforementioned variables are associated with an increase in the stock market index. ConclusionAccording to the obtained results, the price of oil improves market conditions by increasing government revenues and allowing for non-intervention in the stock market. The exchange rate provides the basis for the growth of the stock market index by increasing the profitability of export companies, increasing the profitability of non-export companies through the nominal growth of profits, and increasing the value of assets through the creation of inflation in the economy. Liquidity also affects the improvement of the market on the one hand by creating inflation and on the other hand by increasing market liquidity and prosperity in it. Among the important findings of this research is the positive impact of various macroeconomic variables on the stock market, despite ongoing debates about the negative effects associated with their increase. In particular, the exchange rate and liquidity are two variables whose increases have been correlated with rising inflation in Iran's economy. Therefore, to improve the stock market, the adopted policies need to be comprehensive and avoid partiality. Although increases in these variables may stimulate growth in the stock market, they can also have adverse effects at the macroeconomic level.